БЎЛАЖАК ЖИСМОНИЙ ТАРБИЯ ЎҚИТУВЧИЛАРИНИ ТАЙЁРЛАШДА МОБИЛ ИЛОВАЛАРНИ ҚЎЛЛАШ САМАРАДОРЛИГИ - Тажибаев, С.С.; Олимов, А.И.; Ниязов, А.Т. (SCIENCE and SOCIETY, 2020)
This article describes the results of testing the effectiveness of the mobile application "Physical culture" in teaching the theory of a sabject and methodology of physical culture to the students studying at HEI.
Keywords: physical culture; physical education; mobile applications; development indicators